2013
DOI: 10.4025/actascianimsci.v35i3.18219
|View full text |Cite
|
Sign up to set email alerts
|

<b>Morphology and expression of genes related to skeletal muscle growth in juveniles of pirarucu (<i>Arapaima gigas</i>, Arapaimatidae, Teleostei)</b> - doi: 10.4025/actascianimsci.v35i3.18219

Abstract: ABSTRACT. Skeletal muscle growth in the pirarucu (Arapaima gigas) is highly interesting to fish farmers because it provides information about how the mechanism in muscle mass increase, characteristic of the species, is regulated. Pirarucu has specific muscle growth that highlights the species's significance and commercial value. Current research evaluates the morphology and the growth-related gene expression in the red and white skeletal muscles of the pirarucu. Muscle samples were collected from the lateral a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Many small herbivores have a natural instinct of caecotrophy[1]. Because of the small body shape and their digestive tract volume is limited, the average residence time of food in the digestive tract is relatively short [2, 3]. In order to meet their nutrition needs, small herbivores need to obtain adequate high-quality food[4].…”
Section: Introductionmentioning
confidence: 99%
“…Many small herbivores have a natural instinct of caecotrophy[1]. Because of the small body shape and their digestive tract volume is limited, the average residence time of food in the digestive tract is relatively short [2, 3]. In order to meet their nutrition needs, small herbivores need to obtain adequate high-quality food[4].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the 100 % content of white muscle fibres, the diameters of normal white muscle normal fibres were analysed and then assigned to appropriate classes. Karahmet et al (2014) showed that the average diameter of muscle fibres in rainbow trout (Oncorhynchus mykiss) is in the range 31- hyperplasia and the mechanisms of hypertrophy (Carani et al, 2013). Both hypertrophic and hyperplastic growth result in a large variety of muscle fibre diameters.…”
Section: Histological Analysesmentioning
confidence: 99%